2011
DOI: 10.1007/s00787-011-0194-0
|View full text |Cite
|
Sign up to set email alerts
|

Trajectories of CBCL Attention Problems in childhood

Abstract: The first aim of this study was to identify developmental trajectories of Attention Problems in twins followed from age 6 to 12 years. Second, we investigated whether singletons follow similar trajectories. Maternal longitudinal ratings on the Attention Problems (AP) subscale of the Child Behavior Checklist were obtained for a sample of 12,486 twins from the Netherlands Twin Register and for a general population sample of 1,346 singletons. Trajectories were analyzed by growth mixture modeling in twins, and com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
39
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 41 publications
2
39
0
Order By: Relevance
“…In general, these assumptions have been tested and appear reasonable, for example the equal environments assumption in which monozygotic and dizygotic twins share the same environment to the same extent 64,65 and the assumption of generalisability of twin results to the rest of the population 6668 . In our model fitting analyses we found that the AE model was the best-fitting model.…”
Section: Discussionmentioning
confidence: 99%
“…In general, these assumptions have been tested and appear reasonable, for example the equal environments assumption in which monozygotic and dizygotic twins share the same environment to the same extent 64,65 and the assumption of generalisability of twin results to the rest of the population 6668 . In our model fitting analyses we found that the AE model was the best-fitting model.…”
Section: Discussionmentioning
confidence: 99%
“…7 It identified 3 trajectories in both boys and girls (stable low, low-increasing, and high-decreasing, the latter two crossing). The only apparent difference by sex was that trajectories started and ended lower for girls, with similar slopes.…”
Section: Introductionmentioning
confidence: 99%
“…See “Method” for further details. This sample differs in four ways from most of the others: 1) Unlike the Robbers, Malone, Jester, and Lubke samples, 7-8,10-11,13 it has rigorous standardized clinical diagnoses of ADHD. 2) However, unlike the Swanson and Sonuga-Barke samples, 9,12 it was not selected for a diagnosis of ADHD, but for related (manic) symptoms and therefore includes some children without an ADHD diagnosis but with some ADHD symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Given that research indicates that teacher reported attention problems correspond with an ADHD diagnosis (Derks et al 2006), the use of the TRF is considered an evidence-based, valid method for identifying ADHD symptoms (Pelham et al 2005). Further, precedent exists for using this scale to represent ADHD symptoms in research (Breslau et al 2010; Robbers et al 2011). Results should be replicated with more comprehensive measurement of ADHD symptoms, but correspondence between our measure and ADHD symptoms measured in other ways supports generalization of our results to children with ADHD symptoms.…”
Section: Discussionmentioning
confidence: 99%